Direct C(sp3)–H allylation of 2-alkylpyridines with Morita–Baylis–Hillman carbonates via a tandem nucleophilic substitution/aza-Cope rearrangement - Wang, Siyu; Zheng, Lianyou; Wang, Shutao; Ning, Shulin; Zhang, Zhuoqi; Xiang, Jinbao (Beilstein Journal of Organic Chemistry, 2021)
A base- and catalyst-free C(sp3)–H allylic alkylation of 2-alkylpyridines with Morita–Baylis–Hillman (MBH) carbonates is described. A plausible mechanism of the reaction might involve a tandem SN2’ type nucleophilic substitution followed by an aza-Cope rearrangement. Various alkyl substituents on 2-alkylpyridines were tolerated in the reaction to give the allylation products in 26–91% yields. The developed method provides a straightforward and operational simple strategy for the allylic functionalization of 2-alkypyridine derivatives.
Keywords: 2-alkylpyridines; allylic alkylation; aza-Cope rearrangement; catalyst-free; Morita–Baylis–Hillman carbonates